Is Stability Sufficient? Challenging the Status Quo via Needs Assessment in a 22-Year-Old Student-Run Free Clinic - Gabriella Rizzo; Safwan Elkhatib; Jenenne Geske; Melanie Menning; Hannah Christiansen (Journal of Student-Run Clinics, 2021)
Background: An increase in the utilization of student-run free clinics (SRFCs) as an adjunct to early healthcare student training begs the question of whether SRFCs are meeting expectations of stakeholders, particularly students, faculty, and staff. The objective of our study was to perform a needs assessment of clinic stakeholders to assess whether their expectations regarding clinic purpose and performance were being met.Methods: Clinical leadership at an interdisciplinary SRFC affiliated with an academic medical center in Omaha, Nebraska sent a needs assessment survey to all students, faculty, and staff at the affiliated academic medical center. The responses were coded and analyzed via descriptive statistics.Results: The survey demonstrated that the clinics met key stakeholder priorities in patient care and education and identified some anticipated areas for improvement. It also illuminated several previously unknown and unmet stakeholder expectations, including needs for higher visibility, desire for expanded volunteer roles, discovery of an untapped pool of potential volunteers, and desire for significant improvements to the interdisciplinary process.Conclusions: The needs assessment survey identified specific areas of unmet needs that have implications for the ability of the SRFC to operate and serve patients with quality and efficiency.